Strategi Penentuan Supplier untuk Mitigasi Dampak Kenaikan Harga Bahan Baku pada Industri Manufaktur Baja lapis seng - Muhammad Ibrahim Ats-Tsauri; Isdaryanto Iskandar; Barita Raja Siregar (Universitas Mercu Buana, 2022)
According to the concept of supply chain management, one of the possible solutions for mutual survival in a turbulent world market is chain cooperation among the producer, his suppliers, and customers. The problem of supplier selection and determination of material quantities supplied is one of the most important activities in the supply chain. The purpose of this research is to propose a model for supplier selection for Cold Rolled Coil (CRC) supply by using Analytical Hierarchy Process (AHP), based on decision-making criteria validated by experts in the galvanizing industry. This study found that for galvanizing industry the weight of importance of Cost, Quality, Product, Service, and Delivery criteria is 0.47, 0.19, 0.19, 0.07, and 0.07, respectively. Supplier ranking based on their importance to the industry’s purpose has also been found, which would assist the decision-making process in determining CRC suppliers.